InSAR imaging based on L1 regularisation joint reconstruction via complex approximated message passing. Issue 4 (1st February 2018) - Wu, Chenyang; Wei, Zhonghao; Bi, Hui; Zhang, Bingchen; Lin, Yun; Hong, Wen
Abstract : This Letter presents an interferometric synthetic aperture radar (InSAR) imaging method based on L1 regularisation joint reconstruction model via complex approximated message passing (CAMP). The proposed method enables to ensure the preservation of background information via CAMP and interferometric phase difference information among multiple channels via L1 regularisation joint reconstruction model. Compared with conventional matched filtering results, the proposed method can improve the performance of interferometric phase noise reduction and the continuity of interference fringes, which has broad application prospect in InSAR imaging. Experiments carried out on real data confirmed the effectiveness of the proposed method with improved performance.